Rheumatoid meningitis. Issue 4 (30th March 2016) - Nihat, Akin; Chinthapalli, Krishna; Bridges, Leslie; Johns, Paul; Sofat, Nidhi; Moynihan, Barry
Abstract : Rheumatoid meningitis is a rare, potentially treatable condition that can mimic a wide range of neurological conditions, including vascular syndromes and encephalopathies. Despite a concurrent history of rheumatoid arthritis, patients often have no active synovitis. Here we describe a patient with rheumatoid meningitis who presented to a hyperacute stroke unit with dysarthria on waking and transient facial droop.